EVALUATION OF COMMON ORGANISMS CAUSING VAGINAL DISCHARGE - Khan, Shazia A; Amir, Fauzia; Altaf, Shagufta; Tanveer, Raazia (Journal of Ayub Medical College Abbottabad, 2009)
Background: Vaginal discharge is very common problem among females. Alteration in balance of normal vaginal organisms can cause the overgrowth of the bacteria that creates vaginal discharge. It is common among sexually active women yet there still remain gaps in our knowledge of this infectious disorder. Objective: To evaluate the frequency of bacterial vaginosis (BV), vaginal candidiasis (VC), vaginal trichomoniasis and Group B streptococcus in women complaining of vaginal discharge in our setup. Method: A total of 100 women of reproductive age group with the complaint of vaginal discharge were included in the study. After filling proforma patients were examined by speculum examination and two high vaginal swabs (HVS) were collected aseptically from each patient. One swab was used for making wet mount for clue cells, pus cells and for motility of Trichomonas vaginalis. The other swab was used to check pH and Amine test. The growth was confirmed by Gram staining in each case. Results: Gardnerrella vaginalis were isolated in 28%, Group B streptococcus in 5% and T. vaginolis in 4% of women. Conclusion: Gardnerella vaginalis causing BV is the most common cause of vaginal discharge in otherwise healthy women of reproductive age group in our setup. Keywords: Vaginosis bacterial, Candidiasis, Trichomoniasis, Vaginal Discharge.